Pengembangan Handout Biologi Bermuatan Pendidikan Karakter Pada Materi Perubahan Lingkungan Kelas X SMA - Angela angela; Hamka L; Syamsiah Syamsiah (UNM Journal of Biological Education, 2018)
The aim of this study was to develop biology handout which containing character education in the environmental change material that categorized valid and practical. This is a research and development research (R & D) using the 4D model. Validity of learning materials and material results from 2 expert validators, while practicality resulted from the teacher on the use of learning materials. Development step is done by validation of learning materials of handout, then practiced in SMAN 3 Makassar by 3 biology teachers. Data collection technique used is initial observation, interview and questionnaire. The results showed the validity of learning materials with an average score of 3.7, while the material validity reached an average score of 3.6. Both is in valid category. The results of limited test by the teacher's response obtained an average score of 3.4 and are in the practical category. From what can be reviewed based on validity and practicality, it can be concluded that the learning materials of biology handout which containing character education in the environmental change material was valid and practical.